Peningkatan Kapasitas Organisasi dan Inisiasi Program Bank Sampah Karang Taruna Swayasatwika - Aji, Juhari Sasmito; Pribadi, Ulung (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2024)
The role and function of youth organizations as youth social organizations have an important part in the process of building a village. Maximizing the role and function of youth is currently a major problem in various regions, problems that often arise are due to their inability to function optimally in terms of the ability to formulate work programs. The ability to understand the main tasks and functions of each division or part of the existing organization, such as the youth organization in Kluwih Hamlet, Balecatur, Yogyakarta. In this service program the solutions offered are first, to socialize various regulations and technical technical guidelines, as well as regulations related to the main tasks and functions of karang taruna institutions in general. The socialization also includes the division of tasks from each division, as well as how to arrange activity programs. The implementation method is in the form of socialization of organizational material as well as training in making regulations, preparing programs and activities. From the results of these activities, benefits can be obtained where the Swayasatwika youth organization has succeeded in making a work program regarding the initiation of a waste bank in Kluwih Hamlet. Through the waste bank work program initiated by the Swayasatwika Youth Organization, it is hoped that it can be one of the programs that can maximize the roles and functions of youth in Kluwih Hamlet youth organizations.